PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA ASING (TKA) AKIBAT PEMUTUSAN HUBUNGAN KERJA (PHK) SECARA SEPIHAK OLEH PERUSAHAAN MENURUT UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN (STUDI KASUS PUTUSAN PENGADILAN HUBUNGAN INDUSTRIAL NOMOR 1285/PDT.SUS-PHI/2015/PN.JKT.PST Jo. PUTUSAN MAHKAMAH AGUNG NOMOR 133 K/PDT.SUS-PHI/2017 Jo. PUTUSAN MAHKAMAH AGUNG NOMOR 165 PK/PDT.SUS-PHI/2018) - Hillary Hendry; Stanislaus Atalim (Fakultas Hukum Universitas Tarumanagara, 2019)
Termination of employment is one of the last attempts carried out by the company if no agreement is reached between the parties. However, all efforts must be made in advance so that Termination of Employment does not occur, as stated in Article 151 paragraph (1) of Law No. 13 of 2003 concerning Manpower. The subject matter of this case can be seen from the results of the Judicial Review with Decision Number 165 P / Pdt.Sus-PHI / 2018, stating that the Defendant has unilaterally terminated the Work Relationship and is obliged to pay compensation to the Plaintiff in the form of wages until the IMTA end. Even though according to Article 62 of Law No. 13 of 2003 concerning Labor states that if one party terminates a work relationship before the time expires, the party ending the employment relationship is obliged to pay the worker or labor wage until the expiration of the term of the work agreement. In addition to that, the other main issue is the supervision of the Ministry of Manpower on the use of Foreign Workers (TKA) related to this case. The type of research used is the normative research method.